Can visual methods actually challenge hierarchies? A case study from Papua New Guinea. (24th October 2017) - Simpson Reeves, Laura; Hinthorne, Lauren Leigh
Abstract: Visual research methods continue to be explored as a viable tool within community development, particularly amongst advocates for participatory approaches. It is widely agreed that visual research methods can assist participants in externalizing abstract concepts and create spaces for reflective dialogue. However, these methods are frequently used across the sector with little theorizing or critical reflection. Moreover, visual research methods and participatory processes are often conflated. There is also an assumption that visual research methods, particularly when used in development contexts, can disrupt power structures. This research draws on a case study from Papua New Guinea (PNG) to modestly challenge this assumption and, in doing so, argues for more critical and reflexive practice across community development. The article critically analyses a workshop held in rural PNG in 2013 that employed a visual multimethod approach. The workshop took place over four days with the aim of creating a local community development plan. Perhaps unsurprisingly, we found that while the visual research methods used in PNG demonstrated evidence of shifting some power structures, this was not necessarily because of the method or methods themselves, and was actually more closely linked to the locale in which we facilitated the method(s).